Porous carbon composite and method of making the same
Patent Information
- Application Number
- CN202210160919.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-22
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-02-22
AI Technical Summary
但烧结过程中,升温条件须精准控制,前驱物选择受限,且碳中空纤维成品的微结构与起始的高分子材料差异甚大,致使碳中空纤维无法做更精密的应用
[0004] One objective of this invention is to provide a porous carbon composite material and a method for manufacturing the same. By first depositing a metal compound onto a polymer substrate, the deformation of the polymer substrate into a carbon substrate after heat treatment is restricted, and the structural integrity of the porous carbon composite material can be maintained.
Smart Images

Figure CN116675210B_ABST
Abstract
Description
Technical Field
[0001] The present invention provides a porous carbon composite material and a method for manufacturing the same, particularly a porous carbon composite material that can maintain its original structure and a method for manufacturing the same. Background Technology
[0002] Commercially available porous polymers exhibit excellent gas-liquid separation properties and can be fabricated into hollow fibers, finding wide applications in gas separation and hemodialysis. However, the applicability of polymers is limited by their inability to withstand high temperatures and harsh operating environments. Furthermore, current known techniques for fabricating carbon materials from polymers mostly utilize electrospinning or phase-change wet spinning to create hollow fibers from polymer precursors, which are then sintered to produce carbon hollow fibers. However, the sintering process requires precise temperature control, restricts the selection of precursors, and results in a significant difference in the microstructure of the finished carbon hollow fiber compared to the starting polymer, hindering more precise applications.
[0003] In view of this, improving the manufacturing method of porous carbon composite materials so that the polymer materials can maintain their original structure at both macroscopic and microscopic scales after sintering and carbonization has become the goal of relevant scholars and industry professionals. Summary of the Invention
[0004] One objective of this invention is to provide a porous carbon composite material and a method for manufacturing the same. By first depositing a metal compound onto a polymer substrate, the deformation of the polymer substrate into a carbon substrate after heat treatment is restricted, and the structural integrity of the porous carbon composite material can be maintained.
[0005] One embodiment of the present invention provides a method for manufacturing a porous carbon composite material, comprising providing a polymer substrate, performing a layering step, and performing a heat treatment step. The polymer substrate comprises a polymer compound and has a hollow fiber structure. The polymer substrate has a cross-linked structure located within a tube wall of the hollow fiber structure, and the polymer substrate has multiple pores. The layering step involves depositing a metal compound onto the polymer substrate to form a transition layer. The heat treatment step involves heating the transition layer to carbonize the polymer compound within it, transforming the polymer substrate into a carbon substrate, converting the metal compound into a coating layer, and obtaining the porous carbon composite material. The porous carbon composite material has a one-layer structure.
[0006] In the method for manufacturing porous carbon composite materials according to the foregoing embodiments, the polymer compound may be polyacrylonitrile (PAN), polyimide (PI), cellulose, or polysulfone (PSF).
[0007] In the method for manufacturing porous carbon composite materials according to the foregoing embodiments, the metal compound may be a metal oxide.
[0008] According to the manufacturing method of the porous carbon composite material according to the foregoing embodiments, the layering step can be performed by depositing a metal compound onto a polymer substrate using atomic layer deposition (ALD) or sol-gel methods.
[0009] According to the manufacturing method of the porous carbon composite material according to the above embodiments, the thickness of the metal compound coated on the polymer substrate can be from 1 Å to 2000 Å.
[0010] According to the manufacturing method of the porous carbon composite material according to the above embodiments, the thickness of the metal compound coated on the polymer substrate can be from 50 Å to 2000 Å.
[0011] According to the method for manufacturing porous carbon composite materials according to the foregoing embodiments, the heat treatment step includes a heat treatment temperature, which can be 500°C. o C to 1000 o C.
[0012] In the method for manufacturing porous carbon composite materials according to the foregoing embodiments, the heat treatment step can be carried out under an ammonia atmosphere or an inert gas atmosphere.
[0013] Another embodiment of the present invention provides a porous carbon composite material, which is manufactured by the method for manufacturing porous carbon composite materials of the aforementioned embodiments. The porous carbon composite material has a hollow fiber structure and includes a carbon substrate and a coating layer. The carbon substrate has multiple mesopores and a nano-crosslinked structure located in a tube wall of the hollow fiber structure. The diameter of each mesopore is 2 nm to 50 nm. The coating layer is deposited on the carbon substrate.
[0014] The porous carbon composite material according to the foregoing embodiments, wherein the coating layer may be a metal oxide, a metal nitride, or a metal nitride. Attached Figure Description
[0015] To make the above and other objects, features, advantages and embodiments of the present invention more apparent and understandable, the accompanying drawings are described below: Figure 1 A flowchart illustrating a method for manufacturing a porous carbon composite material according to an embodiment of the present invention is shown; Figure 2A A scanning electron microscope image of the polymer substrate of the present invention; Figure 2B Scanning electron microscope image of the transition material of the present invention; Figure 2C Another scanning electron microscope image of the transition material of the present invention; Figure 2D This is a titanium element distribution diagram of the transition material of the present invention; Figure 3A This is a scanning electron microscope image from Embodiment 1 of the present invention; Figure 3B This is another scanning electron microscope image from Embodiment 1 of the present invention; Figure 3C This is a carbon element distribution diagram of Example 1 of the present invention; Figure 3D This is another scanning electron microscope image of Embodiment 1 of the present invention; Figure 4A This is a scanning electron microscope image from Embodiment 2 of the present invention; Figure 4B This is a carbon element distribution diagram of Example 2 of the present invention; Figure 4C This is another scanning electron microscope image from Embodiment 2 of the present invention; Figure 5A This is a scanning electron microscope image from Embodiment 3 of the present invention; Figure 5B This is a distribution diagram of aluminum element in Example 3 of the present invention; Figure 5C This is another scanning electron microscope image from Embodiment 3 of the present invention; Figure 5D This is a carbon element distribution diagram of Example 3 of the present invention; Figure 6 The scanning electron microscope image of Embodiment 4 of the present invention; and Figure 7 For comparison, the scanning electron microscope image of Example 1. Detailed Implementation
[0016] Several embodiments of the present invention will now be described with reference to the drawings. For clarity, many practical details will be set forth in the following description. However, it should be understood that these practical details are not intended to limit the invention. That is, in some embodiments of the invention, these practical details are not essential. Furthermore, for the sake of simplicity, some conventional structures and components will be shown in the drawings in a simple schematic manner; and repeated components may be denoted by the same number.
[0017] Please see Figure 1 The flowchart illustrates a method for manufacturing a porous carbon composite material according to an embodiment of the present invention, which includes steps 110, 120 and 130, each of which will be described in detail below.
[0018] Step 110 involves providing a polymer substrate comprising a polymer compound and having a plurality of pores. More specifically, the polymer substrate has a cross-linked structure (e.g., Figure 2A As shown), the cross-linked structure forms multiple pores, and the polymer substrate is mesoporous. Specifically, the polymer compound may be polyacrylonitrile (PAN), polyimide (PI), cellulose, polysulfone (PSF), or other carbonizable organic compounds, and the present invention is not limited to the content disclosed herein.
[0019] Step 120 involves a layering process in which a metal compound is deposited onto a polymer substrate to form a transition material. The layering process can utilize atomic layer deposition (ALD) or sol-gel methods to deposit the metal compound onto the polymer substrate. This allows the metal compound to more uniformly and completely coat the polymer substrate and its cross-linked structures.
[0020] Specifically, the metal compound may be any metal oxide. For example, the metal oxide may be manganese oxide, zirconium oxide, tungsten oxide, hafnium oxide, tantalum oxide, vanadium oxide, niobium oxide, chromium oxide, molybdenum oxide, cerium oxide, zinc oxide, titanium oxide, aluminum oxide, silicon oxide, copper oxide, nickel oxide, iron oxide, cobalt oxide, tin oxide, gallium oxide, germanium oxide, or a combination thereof. This invention is not limited to the contents disclosed herein.
[0021] If atomic layer deposition (ALD) is used in step 120, in practice, a precursor is first introduced and adhered to the polymer substrate, followed by the introduction of an inert gas to remove unreacted precursors and byproducts. Next, a co-reactant is introduced to react with the precursor, and another inert gas is introduced to remove unreacted precursors and byproducts. This process is called a cycle, and each cycle grows a film only one atomic layer thick. Therefore, the thickness of the metal compound deposited on the polymer substrate can be further controlled by controlling the number of cycles in the ALD process. In the method 100 for manufacturing the porous carbon composite material of the present invention, the layering step can be repeated 1 to 2000 times, more preferably 50 to 2000 times, to form a sufficient thickness. The thickness of the metal compound deposited on the polymer substrate can be 1 Å to 2000 Å, more preferably 50 Å to 2000 Å.
[0022] Step 130 involves a heat treatment step, which heats the transition material to carbonize the polymer compounds within it, transforming the polymer substrate into a carbon substrate and the metal compound into a coating layer, thereby obtaining a porous carbon composite material. This porous carbon composite material may have a hierarchical structure. Specifically, the heat treatment step can be performed in an ammonia atmosphere or an inert gas atmosphere, and the heat treatment step may have a heat treatment temperature, which may be 500°C. o C to 1000 o C, the transition material can be heated at a heating rate of 1. o C / min to 50 o The temperature is C / min, and the heat treatment process can last from 0.5 hours to 72 hours.
[0023] Specifically, the operating conditions of the heat treatment steps can be determined based on the characteristics of the metal compound, the characteristics of the polymer substrate, and the degree of carbonization. Depending on the heat treatment conditions, the coating layer converted from the metal compound can be a metal oxide, a metal oxynitride, or a metal nitride. Furthermore, the method 100 for manufacturing porous carbon composite materials of the present invention can manufacture porous carbon composite materials containing metal oxides (metal oxide@C), porous carbon composite materials containing metal oxynitrides (metal oxynitride@C), and porous carbon composite materials containing metal nitrides (metal nitride@C), but the present invention is not limited thereto.
[0024] Through the above-described method 100 for manufacturing porous carbon composite materials, a porous carbon composite material is finally obtained. This porous carbon composite material comprises a carbon substrate and a coating layer, with the coating layer deposited on the carbon substrate. The carbon substrate has multiple mesoporous pores with a diameter of 2 nm to 50 nm. More specifically, the carbon substrate has a nano-crosslinked structure (such as...). Figure 3B As shown, the nano-crosslinked structure forms multiple mesopores.
[0025] The porous carbon composite material of this invention can be a hollow fiber structure or a carbon aerogel structure. Specifically, hollow fibers have good gas and liquid separation properties and can be widely used in gas separation and hemodialysis. Carbon aerogels have multiple applications, such as energy storage, catalysis, gas storage, wastewater treatment, and heat insulation. The manufacturing method 100 of the porous carbon composite material of this invention can improve the durability of the above-mentioned applications and further expand their application scope.
[0026] In the manufacturing method 100 of the porous carbon composite material of the present invention, a metal compound is uniformly deposited onto the polymer substrate and its cross-linked structures. This allows the metal compound to restrict the transformation of the polymer substrate into carbon and helps maintain the structural integrity of the carbon substrate and its nano-cross-linked structures in the porous carbon composite material. More specifically, the metal compound deposit prevents damage to the structure of the polymer substrate during the carbonization process in the heat treatment step, and ensures that the structural morphology of the carbon substrate and its nano-cross-linked structures in the porous carbon composite material is consistent with that of the polymer substrate and its cross-linked structures. Therefore, by controlling the structure of the polymer substrate, the macroscopic and microscopic structure of the porous carbon composite material can be controlled, allowing for more precise and accurate control over the morphology and structure of the porous carbon composite material. Furthermore, the carbonization of the polymer compound into carbon can impart electrical conductivity and improve the chemical stability of the porous carbon composite material, thereby increasing its applications.
[0027] It is worth noting that conventional methods for manufacturing porous carbon composite materials utilize electrospinning or phase change wet spinning techniques. These methods involve mixing polymer precursors with other substances, processing them into a predetermined structure, such as hollow fibers, and then sintering them into porous carbon materials. However, during sintering, precise temperature control is required to maintain the structural integrity of the pores, limiting the selection of polymer precursors. Furthermore, the resulting porous carbon composite material and its microstructure differ significantly from the initial polymer material's microstructure, hindering its ability to meet more precise requirements and thus limiting its development. Compared to conventional methods for manufacturing porous carbon composite materials, the method 100 of this invention allows for faster carbonization, reducing process time, while maintaining the structural consistency with the original polymer substrate. Therefore, the macroscopic and microscopic structures of the porous carbon composite material of this invention can be more precisely controlled, thereby meeting more sophisticated application requirements.
[0028] The present invention will be further illustrated by the following specific embodiments, which are intended to enable those skilled in the art to fully utilize and practice the invention without excessive interpretation. These embodiments should not be regarded as limiting the scope of the invention, but are used to illustrate how to implement the materials and methods of the invention.
[0029] <Example / Comparative Example>
[0030] To illustrate more precisely the advantages of the manufacturing method 100 for porous carbon composite materials of the present invention, Examples 1, 2, 3, 4, and Comparative Example 1 are presented. Examples 1, 2, 3, and 4 are porous carbon composite hollow fibers produced using the manufacturing method 100 for porous carbon composite materials, while Comparative Example 1 is a porous carbon material that has undergone direct heat treatment without being coated with a metal compound. In Examples 1 to 4, the polymer substrate used is polysulfone.
[0031] Specifically, Example 1 is a porous carbon composite hollow fiber containing nitrogen-containing titanium oxide (TiO2). x N 1-x Example 2 is a porous carbon hollow fiber containing titanium nitride (TiN@carbon hollow fiber); Example 3 is a porous carbon hollow fiber containing alumina (Al2O3@carbon hollow fiber); and Example 4 is a porous carbon hollow fiber containing nitrogen-containing titanium oxide (TiO3@carbon hollow fiber) prepared by the sol-gel method. x N 1-x The manufacturing methods of each embodiment will be described below (@carbon hollowfiber).
[0032] In the preparation of Examples 1 and 2, titanium dioxide was deposited onto polysulfone using atomic layer deposition (ALD), and the ALD process was repeated 400 times. Following this, heat treatment was performed in an ammonia atmosphere at a temperature of 800°C. o C, by carbonizing the polysulfone and converting the titanium dioxide into titanium oxynitride, Example 1 can be obtained; additionally, if the heat treatment temperature is set to 1000... o C. By completely nitriding titanium dioxide to form titanium nitride, Example 2 can be obtained.
[0033] In preparation Example 3, alumina was deposited onto polysulfone using atomic layer deposition (ALD), and the ALD process was repeated 200 times. Following this, heat treatment was performed under an argon atmosphere at a temperature of 800°C. o C, by carbonizing polysulfone, the alumina is transformed into the γ crystalline phase, thus obtaining Example 3.
[0034] In the preparation of Example 4, polysulfone was first immersed in a titanium isopropoxide solution (TTIP, 1 wt%) diluted with isopropanol (IPA). Air bubbles inside the polysulfone were removed by ultrasonic agitation, and the titanium isopropoxide solution filled the polysulfone onto its nano-crosslinked structure. Next, the polysulfone coated with titanium isopropoxide was removed from the titanium isopropoxide solution and air-dried, during which the titanium isopropoxide reacted with moisture in the air to form titanium dioxide. This was then subjected to a nitriding heat treatment to convert it into titanium oxynitride, thus obtaining Example 4.
[0035] Please refer to Figures 2A to 2D . Figure 2A This is a scanning electron microscope image of the polymer substrate of the present invention. Figure 2B This is a scanning electron microscope image of the transition material of the present invention. Figure 2C Another scanning electron microscope image of the transitional material of the present invention. Figure 2D This is a titanium element distribution diagram of the transition material of the present invention.
[0036] To be precise, Figures 2A to 2D This image shows the transition material in the method 100 for manufacturing the porous carbon composite material of the present invention, and Figures 2A to 2C These are scanning electron microscope images at different magnifications. Figures 2A to 2D The analysis results show that titanium is uniformly distributed on the surface of the polymer substrate and its cross-linked structure. This indicates that atomic layer deposition can be used to completely and uniformly coat titanium dioxide onto the polymer substrate, and can further ensure the structural integrity after the heat treatment step.
[0037] Please refer to Figures 3A to 3D . Figure 3A This is a scanning electron microscope image of Embodiment 1 of the present invention. Figure 3B This is another scanning electron microscope image according to Embodiment 1 of the present invention. Figure 3C This is a carbon element distribution diagram of Embodiment 1 of the present invention. Figure 3D This is another scanning electron microscope image of Embodiment 1 of the present invention.
[0038] To be precise, Figure 3A , Figure 3B and Figure 3D Images are scanning electron microscope images at different magnifications, such as... Figure 3A As shown, after the heat treatment step, the macrostructure of Example 1 remains quite intact, and as Figure 3B and Figure 3D As shown, the structural morphology of the nano-crosslinked structure in Example 1 is also quite complete. Furthermore, as... Figure 3C As shown, the carbon element is distributed quite evenly, indicating that the polymer substrate has been completely carbonized into a carbon substrate.
[0039] Please refer to Figures 4A to 4C . Figure 4A This is a scanning electron microscope image of Embodiment 2 of the present invention. Figure 4B This is a carbon element distribution diagram of Embodiment 2 of the present invention. Figure 4C This is another scanning electron microscope image from Embodiment 2 of the present invention.
[0040] like Figure 4A and Figure 4CAs shown, the analysis results of scanning electron microscopy at different magnifications indicate that after the higher temperature heat treatment step, the macroscopic structure and nano-crosslinked structure of Example 2 remained quite intact and were almost identical to the structure of the polymer substrate before heat treatment. Furthermore, as... Figure 4B As shown, the carbon element is distributed quite evenly, indicating that the polymer substrate has been completely carbonized into a carbon substrate.
[0041] Please refer to Figures 5A to 5D . Figure 5A This is a scanning electron microscope image of Embodiment 3 of the present invention. Figure 5B This is an aluminum element distribution diagram of Embodiment 3 of the present invention. Figure 5C This is another scanning electron microscope image according to Embodiment 3 of the present invention. Figure 5D This is a carbon element distribution diagram of Example 3 of the present invention.
[0042] like Figure 5A and Figure 5C As shown, the analysis results of scanning electron microscopy at different magnifications show that after the heat treatment step, the macroscopic structure and its nano-crosslinked structure of Example 3 remain quite intact and are almost identical to the structure of the polymer substrate before heat treatment. Furthermore, as... Figure 5B and Figure 5D As shown, the aluminum and carbon elements are distributed quite evenly, indicating that the polymer substrate has been carbonized into a carbon substrate and uniformly coated with aluminum oxide.
[0043] Please refer to Figure 6 This is a scanning electron microscope image from Embodiment 4 of the present invention. Figure 6 As shown, a complete composite nano-crosslinked structure can be obtained by coating titanium dioxide onto polysulfone using the sol-gel method.
[0044] Please refer to Figure 7 This is a scanning electron microscope image of Comparative Example 1. Specifically, Comparative Example 1 is a carbon material that underwent direct heat treatment without being coated with a metallic compound. Figure 7 As shown, the nano-crosslinked structure and mesoporous structure of Comparative Example 1 have been completely destroyed, and Comparative Example 1 can no longer exert its porous properties, thus limiting its application.
[0045] As can be seen from the above analysis, compared with Comparative Example 1, Examples 1 to 4 of the present invention, regardless of their macroscopic or nano-crosslinked structures, show no serious damage and maintain good structural integrity, and are almost identical to the original polymer substrate structure. Therefore, the detailed structure of the porous carbon composite material of the present invention can be more precisely controlled, thereby meeting more sophisticated application requirements.
[0046] Although the present invention has been disclosed above by way of embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various modifications and refinements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be determined by the appended claims.
[0047] Symbol explanation: 100: Manufacturing method of porous carbon composite materials 110, 120, 130: Steps
Claims
1. A method for manufacturing a porous carbon composite material, characterized in that, Include: A polymer substrate is provided, the polymer substrate comprising a polymer compound, the polymer substrate having a hollow fiber structure, the polymer substrate having a crosslinking structure located in a tube wall of the hollow fiber structure, and the polymer substrate having a plurality of pores. A layering step is performed to deposit a metal compound onto the polymer substrate, forming a transition material; and A heat treatment step is performed to heat the transition material, causing the polymer compound in the transition material to carbonize, transforming the polymer substrate into a carbon substrate, transforming the metal compound into a coating layer, and obtaining a porous carbon composite material having a one-layer structure.
2. The method for manufacturing porous carbon composite material as described in claim 1, characterized in that, The polymer is polyacrylonitrile, polyimide, cellulose, or polysulfone.
3. The method for manufacturing porous carbon composite materials as described in claim 1, characterized in that, The metal compound is a metal oxide.
4. The method for manufacturing porous carbon composite material as described in claim 1, characterized in that, The layering step involves depositing the metal compound onto the polymer substrate using either atomic layer deposition or a sol-gel method.
5. The method for manufacturing porous carbon composite material as described in claim 1, characterized in that, The thickness of the metal compound deposited on the polymer substrate ranges from 1 Å to 2000 Å.
6. The method for manufacturing porous carbon composite material as described in claim 5, characterized in that, The thickness of the metal compound deposited on the polymer substrate ranges from 50 Å to 2000 Å.
7. The method for manufacturing porous carbon composite material as described in claim 1, characterized in that, This heat treatment step has a heat treatment temperature of 500°C. o C to 1000 o C.
8. The method for manufacturing porous carbon composite material as described in claim 1, characterized in that, The heat treatment step is carried out in an ammonia atmosphere or an inert gas atmosphere.
9. A porous carbon composite material, manufactured by the method for manufacturing the porous carbon composite material according to any one of claims 1 to 8, characterized in that, The porous carbon composite material has a hollow fiber structure and comprises: The carbon substrate has multiple mesopores and a nano-crosslinked structure located within a tube wall of the hollow fiber structure; each of the mesopores has a diameter of 2 nm to 50 nm; and The coating is deposited on the carbon substrate.
10. The porous carbon composite material as described in claim 9, characterized in that, The coating is a metal oxide, metal nitride, or metal nitride.